Educação para a geoconservação no território do Geoparque Corumbataí, SP - Kolya, André de Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The territory of the Corumbataí Geopark Project, located in the state of São Paulo, is a region rich in geodiversity and elements of geoheritage. Encompassing local sequences of the Paraná Basin, the region is notable for the outcrop zones of the Guarani Aquifer System, the type section of the Assistência Member of the Irati Formation, and the landscape of cuestas and residual hills of the transition between regional geomorphological provinces. In this context, the region has been developing a UNESCO Global Geopark project since 2016. This work studies the foundations and actions aimed at education and the popularization of Geosciences within the scope of the Project, with the objective of characterizing, proposing, and evaluating geoconservation strategies applied in this regard. The study started with a theoretical framework based on literature, UNESCO documents, and the experience of other Geoparks. The research was conducted as a case study, through immersion in the territory and networking with various local stakeholders. Exchanges between the community and the researcher provided the basis for the strategies and educational materials presented. These products were developed, applied, and revised to fit the local reality and the needs of the Geopark Project. Questionnaires and evaluations from the research participants demonstrated the effectiveness of the proposed methods and materials. Thus, the knowledge generated was systematized into collections of materials, educational platforms, and activity sheets, with the aim of creating an education program for the Geopark, thereby contributing to the future candidacy of the Corumbataí Geopark Project to the UNESCO Global Geoparks and Geosciences Program.

O território do Projeto Geoparque Corumbataí, no interior do estado de São Paulo, é uma região rica em geodiversidade e elementos do geopatrimônio. Abrangendo as sequências paulistas da Bacia do Paraná, a região se destaca pelas zonas de afloramento do Sistema Aquífero Guarani, pela seção tipo do Membro Assistência da Formação Irati e pela paisagem de cuestas e morros testemunhos da transição entre grandes províncias geomorfológicas. Nesse contexto, a região vem desenvolvendo, desde 2016, um projeto de Geoparque Mundial da UNESCO. Este trabalho estuda as bases e ações voltadas à educação e à popularização das Geociências no âmbito do Projeto e tem como objetivo caracterizar, propor e avaliar estratégias de geoconservação aplicadas nesse sentido. O estudo partiu de um conceitual teórico, com base na literatura, nos documentos da UNESCO e na experiência de outros Geoparques. A pesquisa foi conduzida como um estudo de caso, a partir da imersão no território e no trabalho em rede com diversos atores locais. As trocas entre a comunidade e o pesquisador forneceram a base para as estratégias e materiais didáticos apresentados. Estes produtos foram desenvolvidos, aplicados e revisados, moldando-os à realidade local e às necessidades dos envolvidos no Geoparque. Questionários e avaliações do público participante da pesquisa demonstraram a efetividade dos métodos e materiais propostos. Dessa forma, o conhecimento gerado foi sistematizado em coleções de materiais, plataformas didáticas e fichas de atividades, com vistas à elaboração de um programa de educação para o Geoparque, contribuindo assim, para a futura candidatura do Projeto Geoparque Corumbataí ao Programa Internacional de Geociências e Geoparques e à Rede de Geoparques Mundiais da UNESCO.
Education for geoconservation in Corumbataí Geopark territory
Educación para la conservación geológica en el territorio del Geoparque Corumbataí
Keywords: Educação para a geoconservação; Divulgação e popularização das geociências; Didática; Participação comunitária; Geoparques; Education for geoconservation; Dissemination and popularization of geosciences; Didactics; Community participation